2011
DOI: 10.1128/aac.05044-11
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Phase II, Multicenter Study Evaluating the Safety/Tolerability and Efficacy of JNJ-Q2, a Novel Fluoroquinolone, Compared with Linezolid for Treatment of Acute Bacterial Skin and Skin Structure Infection

Abstract: JNJ-Q2 is a fluoroquinolone with broad coverage including methicillin-resistant Staphylococcus aureus (MRSA). A double-blind, multicenter, phase II noninferiority study treated 161 patients for 7 to 14 days, testing the efficacy of JNJ-Q2 (250 mg, twice a day [BID]) versus linezolid (600 mg, BID) in patients with acute bacterial skin and skin structure infections (ABSSSI). The prespecified criterion for noninferiority was 15%. Primary intent-to-treat analysis was unable to declare noninferiority, as the risk d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 24 publications
0
44
1
Order By: Relevance
“…JNJ-Q2 possesses desirable drug-like properties, including acceptable solubility and lipophilicity. In a phase 2 clinical trial comparing efficacy, safety, and tolerability to those of linezolid, it was found to be statistically noninferior for early clinical response and well tolerated, with a favorable safety profile (32). However, primary intent-to-treat analysis was unable to declare noninferiority based on a 15% delta (a measure of comparison between arms of a controlled clinical trial that is related to a confidence interval); additional clinical data will be required for further development.…”
Section: Quinolonesmentioning
confidence: 99%
“…JNJ-Q2 possesses desirable drug-like properties, including acceptable solubility and lipophilicity. In a phase 2 clinical trial comparing efficacy, safety, and tolerability to those of linezolid, it was found to be statistically noninferior for early clinical response and well tolerated, with a favorable safety profile (32). However, primary intent-to-treat analysis was unable to declare noninferiority based on a 15% delta (a measure of comparison between arms of a controlled clinical trial that is related to a confidence interval); additional clinical data will be required for further development.…”
Section: Quinolonesmentioning
confidence: 99%
“…In conclusion, three (5%) and zero patients discontinued the study drug because of adverse reactions attributable to GSK1322322 and linezolid, respectively. In comparison, 0.6 to 2.6% of the patients treated with linezolid were discontinued from other previous phase II or III trials (5,24,25). Therefore, the frequency of withdrawal observed in this study suggests that the tolerability of the 1,500-mg b.i.d.…”
Section: Discussionmentioning
confidence: 74%
“…No early clinical treatment response was reported in the proxy for placebo uSSTI trials. The early clinical treatment response for linezolid in the ITT population was reported in three trials, with a pooled estimate of 78.7% (95% CI, 61.1% to 96.3%); a high variance across trials (I 2 ϭ 96.7%, P Ͻ 0·0001) was evident (39,41,42). This response rate approximated the early clinical treatment response rate of 79.4% (95% CI, 75.1% to 83.7%) reported in the most robust of the three linezolid trials with these data, as well as the early clinical treatment response of ceftaroline at 74.0% (95% CI, 69.7% to 78.3%) reported in one trial (39,54).…”
Section: Iii) Nonantibacterial Treatment Trials (Search C)mentioning
confidence: 99%
“…These trials, published over a 13-year interval, had evidence of clinical and methodological heterogeneity for lesion size, type of infection, geographic region, MRSA etiology, per-protocol treatment duration, definition of clinical success, and timing of TOC assessment (Tables 2 and 3). For the meta-analysis, the selection of the three linezolid trials comprised subjects with total surface area lesion size of Ն75 cm 2 , non-MRSA-specific populations, and Ͻ50% of subjects with abscesses (39,41,42). The pooled linezolid TOC clinical treatment response rate was 88.1% (95% CI, 81.0% to 95.1%) (Fig.…”
Section: Iii) Nonantibacterial Treatment Trials (Search C)mentioning
confidence: 99%
See 1 more Smart Citation